2013
DOI: 10.1088/0266-5611/29/11/115008
|View full text |Cite
|
Sign up to set email alerts
|

On a continuation approach in Tikhonov regularization and its application in piecewise-constant parameter identification

Abstract: We present a new approach to convexification of the Tikhonov regularization using a continuation method strategy. We embed the original minimization problem into a one-parameter family of minimization problems. Both the penalty term and the minimizer of the Tikhonov functional become dependent on a continuation parameter.In this way we can independently treat two main roles of the regularization term, which are stabilization of the ill-posed problem and introduction of the a priori knowledge. For zero continua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The ASM is used in many different fields, such as control theory (Lions, 1971), data assimilation in meteorology (Lewis et al, 2006) or parameter identification (Melicher and Vrábel', 2013;Cimrák and Melicher, 2007). It is difficult to precisely trace its origin, since it is based on a general principle -the duality.…”
Section: Adjoint-state Methodsmentioning
confidence: 99%
“…The ASM is used in many different fields, such as control theory (Lions, 1971), data assimilation in meteorology (Lewis et al, 2006) or parameter identification (Melicher and Vrábel', 2013;Cimrák and Melicher, 2007). It is difficult to precisely trace its origin, since it is based on a general principle -the duality.…”
Section: Adjoint-state Methodsmentioning
confidence: 99%
“…In some cases, small varieties in the right-hand side of (15) may lead to dramatic varieties in the solution [25][26][27][28]. In other words, they are very susceptible to error, in the inverse problem, this may directly lead to greater deviations of the identified results [29][30][31], and thus it is not realistic to solve (15) using traditional mathematical methods [32][33][34].…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…J. Gao et al [12] utilized the standard TR method for identifying the unknown load source. V. Melicher et al [13] identified the piecewise constant parameter using the standard TR method. In addition, many works are mainly concerned with the identification of load position and load number in nonlinear system using the standard TR method [14][15][16].…”
Section: Introductionmentioning
confidence: 99%